Acoustic Correlates of Auditory Object and Event Perception: Speakers, Musical Timbres, and Environmental Sounds - Ogg, Mattson; Slevc, L. Robert (Frontiers in Psychology, 2019)
Human listeners must identify and orient themselves to auditory objects and events in their environment. What acoustic features support a listener’s ability to differentiate the great variety of natural sounds they might encounter? Studies of auditory object perception typically examine identification (and confusion) responses or dissimilarity ratings between pairs of objects and events. However, the majority of this prior work has been conducted within single categories of sound. This separation has precluded a broader understanding of the general acoustic attributes that govern auditory object and event perception within and across different behaviorally relevant sound classes. The present experiments take a broader approach by examining multiple categories of sound relative to one another. This approach bridges critical gaps in the literature and allows us to identify (and assess the relative importance of) features that are useful for distinguishing sounds within, between and across behaviorally relevant sound categories. To do this, we conducted both behavioral sound identification (Experiment 1) and dissimilarity rating (Experiment 2) studies using a broad set of stimuli that leveraged the acoustic variability within and between different sound categories via a diverse set of 36 sound tokens (12 utterances from different speakers, 12 instrument timbres, and 12 everyday objects from a typical human environment). Multidimensional scaling solutions as well as analyses of trial-level responses as a function of different acoustic qualities were used to understand what acoustic features informed participants’ responses. In addition to the spectral and temporal envelope qualities noted in previous work, listeners’ dissimilarity ratings were associated with spectrotemporal variability and aperiodicity. Subsets of these features (along with fundamental frequency variability) were also useful for making specific within or between sound category judgments. Dissimilarity ratings largely paralleled sound identification performance, however the results of these tasks did not completely mirror one another. In addition, musical training was related to improved sound identification performance.